2017
DOI: 10.3389/fimmu.2017.00416
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle Interactions with the Immune System: Clinical Implications for Liposome-Based Cancer Chemotherapy

Abstract: The development of stable and long-circulating liposomes provides protection of the drug cargo from degradation and increases tumor drug delivery, leading to the design of liposome formulations with great potential in cancer therapy. However, despite the sound pharmacologic basis, many liposomal as well as other nanoparticle-based drug formulations have failed to meet regulatory criteria for approval. The question that arises is whether we have missed key liposome–host interactions that can account for the gap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
70
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 48 publications
1
70
0
Order By: Relevance
“…In the present study, we investigated the potential for reprogramming of circulating innate immune cells through NP administration to enhance functional regeneration following SCI. When innate immune cells are activated in the blood and spleen, they have high phagocytic capacity for scavenging apoptotic cells, cellular debris, and foreign invasive materials (24,25). Generally, NPs may be perceived by inflammatory monocytes and neutrophils as foreign material and are then rapidly internalized (13,26,27).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we investigated the potential for reprogramming of circulating innate immune cells through NP administration to enhance functional regeneration following SCI. When innate immune cells are activated in the blood and spleen, they have high phagocytic capacity for scavenging apoptotic cells, cellular debris, and foreign invasive materials (24,25). Generally, NPs may be perceived by inflammatory monocytes and neutrophils as foreign material and are then rapidly internalized (13,26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Aminobisphosphonates have been shown to have immune stimulatory effects such as induction of proinflammatory cytokines, sensitization of macrophages to inflammatory stimuli, and activation of gamma-delta T-cells [57]. In contrast, non-aminobisphosphonates such as clodronate, primarily act via production of toxic ATP analogues and have been shown to inhibit production of inflammatory mediators and cause overall macrophage suppression and toxicity [18,57]. Encapsulation of alendronate into liposomes is likely to modify the immune modulatory effects of the drug, as the carrier will dictate the pharmacokinetic profile and may drastically alter cellular and molecular interactions.…”
Section: Discussionmentioning
confidence: 99%
“…EPR was described for the first time by Maeda and co-workers [43]. Also, it is demonstrated that EPR effect is the major mechanism for the selective accumulation of nanotherapeutics in tumors [44]. Nanocarrier therapies such as PEGylated liposomes have been extensively utilized as drug delivery system to achieve tumor tissues targeting via EPR effect.…”
Section: Tumor Accumulation Of Pegylated Liposomes Via Epr Effectmentioning
confidence: 99%
“…Moreover, Yang and Lai reported an even higher titers of PEG-antibodies of about 42 % in patients with no history of treatment with PEGylated products [52]. Also pre-existing anti-PEG antibodies may be represented in 56-72 % of people [44]. This could be explained by some researchers due to the common use of PEG products.…”
Section: Immunogenicity Of Pegmentioning
confidence: 99%
See 1 more Smart Citation